Traducción de una selección de poemas de Caitlín Maude y de Mary O’Malley al español - Pura López Colomé; Enrique Alda (Estudios Irlandeses, 2019)
Upon reading Seamus Heaney’s early poetry collections – and this was a long time ago – I was surprised by his subtle way of offering up his own versions of poems by other authors as a way to making them his own and moulding them with exacting precision into the specific theme of each given collection. Rather than referring to them as “translations”, he used the word after as an antecedent (to works by the likes of Dante, Baudelaire, Virgil, and some Gaelic authors) with the aim of reworking them into newly inspired viewpoints a posteriori; thus, the poem’s metaphors and images, initially belonging to a different language, would be born again, this time to a different voice and melody – his own – in such a way that his harmonious yet elusive “music of events” was crafted into something visible and audible. I owe this great Captain the sudden epiphany of conceiving translation as creation, as an opportunity of feeding foreign sounds to a symphony of musical inimitability. As time went on, I had the chance to be present at some of his poetry readings, attended by audiences of varying sizes, where – to put it this way – “the yellow bittern”, otherwise known as the seventeenth-century “An Bunnán Bui”, would take flight in yet another twentieth-century poem by Heaney.